Klasterisasi Penerima Bantuan Sosial Menggunakan Metode Simple Additive Weighting - Dison Librado; Tri Prabawa; Heru Agus Triyanto (JURNAL INFORMATIKA DAN KOMPUTER, 2023)
This research is about a decision support system using the Simple Additive Weighting method to help determine the recipients of social assistance wich provided by the government with the aim to improve their standard of living. Wedomartani Village has a fairly large area with a large population. The problem is that the number of potential beneficiaries is not proportional to the available social assistance quota, so it is necessary to select recipients based on certain criteria to fit the target. The Simple Additive Weighting (SAW) method has been used to determine the nomination of candidates for social assistance. From the results of data processing for prospective recipients of Bantuan Langsung Tunai Dana Desa (BLT-DD) in 2020, If the largest 25 are taken from it, it shows that the distribution of the poverty level of the population in the area is not evenly distributed, so a policy made by the sub-district government is needed for more specific poverty reduction.